Skill Of Public Speaking Lab for Islamic Finance Management Study Program Students, IAIN Parepare - damianti, darmianti (Makkareso: Riset Pengabdian Masyarakat, 2023)
During the training, the participants always arrived on time and were very enthusiastic in listening to the explanations from the servants. The participants were also very active in the discussion sessions and asked lots of questions. They are very aware that the ability to speak public is very useful for them, not only for their daily lives but also to help improve their presentation skills on campus. The result of this student-based service is giving birth to a public speaking community not only at the faculty level but also at the institute level.